Approach on chitosan/virgin coconut oil-based emulsion matrices as a platform to design superabsorbent materials. (1st December 2020) - Silva, Simone S.; Rodrigues, Luísa C.; Fernandes, Emanuel M.; Gomes, Joana M.; Vilas-Boas, Ângela; Pirraco, Rogério P.; Reis, Rui L.
Graphical abstract: Highlights: Stable and flexible CHT/VCO-based films were obtained without surfactants use. Emulsion films capable of absorbing 4.5 times their weight in water. The features of the films can be tuned by changing the virgin coconut content into them. Emulsion films extracts suggested good hASCs cell viability without associated cellular damage Abstract: The design of innovative pharmaceutical products, able to reach unexplored market niches, requires natural materials use with improved swelling and moisture properties. Herein, chitosan (CHT), a natural polymer, was combined with virgin coconut oil (VCO), a resource extracted from coconut kernels, to develop emulsion-based films for biomedical purposes. The film's properties were tuned by changing VCO concentrations, and the structural, morphological, and physical properties of the films were evaluated. The CHT/VCO-based film morphology showed the presence of VCO droplets at different sizes, both in the surface and inner part. Moreover, the capability to develop CHT/VCO-films as superabsorbent materials was shown. The film extracts cytotoxicity was assessed using human adipose stem cells, and metabolic activity was confirmed. The findings suggest that incorporating a small volume of VCO into the CHT system, superabsorbent materials with the potential to be applied in biomedical devices that require high swelling properties, can be developed.